2020
DOI: 10.1371/journal.pone.0234208
|View full text |Cite
|
Sign up to set email alerts
|

Diverse subterranean fungi of an underground iron ore mine

Abstract: Mines and caves are unusual ecosystems containing unique fungi and are greatly understudied compared to other environments. The Soudan Mine in Tower, MN, an iron ore mine that closed in 1963 after operating for 80 years, was sampled to explore fungal diversity and to investigate taxa that tolerate heavy metals for potential bioprocessing technologies or as sources of bioactive molecules for drug discovery and possible biocontrol for white-nose syndrome (WNS) of bats. The mine is 714 m deep, has 18 levels and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 66 publications
1
13
0
Order By: Relevance
“…Subsequently, other studies added more fungal taxa to that list, increasing the number of fungi found in caves [e.g. 11 , 15 18 , 20 27 , 64 , 71 , 80 , 81 ]. In two karst caves in China, Zhang et al [ 16 ] reported that 28 (24%) of the 116 genera and 111 (59%) of the 188 identified species were reported for the first time in cave environments.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, other studies added more fungal taxa to that list, increasing the number of fungi found in caves [e.g. 11 , 15 18 , 20 27 , 64 , 71 , 80 , 81 ]. In two karst caves in China, Zhang et al [ 16 ] reported that 28 (24%) of the 116 genera and 111 (59%) of the 188 identified species were reported for the first time in cave environments.…”
Section: Discussionmentioning
confidence: 99%
“…Mortierella sp. have been found from different hostile environments including hydrocarbon contaminated soils and heavy metal rich underground iron ore mines [ 87 , 88 ]. They have been shown to produce nitrous oxide (N 2 O), and host Burkholderia -related endosymbiotic bacteria [ 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there were some differences in the respective compositions of some long-chain fatty acids, such as C18:1 ω5c, C19:0 iso, and C20:1 ω7c. The respiratory quinones of strains NC18 T and NC20 were Q-10, typical for the genus Martelella [ 1 , 2 , 3 , 4 , 5 , 6 ].…”
Section: Resultsmentioning
confidence: 99%
“…The mine reaches a depth of 714 m below the surface, providing access to deep subsurface brines entrained in a massive hematite formation [ 3 , 4 ]. Previous cultivation-based and metagenomics studies reported the presence of diverse microbial communities, including the iron-oxidizing Marinobacter and iron-reducing Desulfuromonas in a calcium- and sodium-rich brine that reaches salinities as high as 4.2% ( w / v ) from these boreholes [ 3 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%